Biomechanical Analysis of Conventional Partially Threaded Screws Versus Headless Compression Screws in Proximal Fifth Metatarsal (Jones) Fracture Fixation. Issue 6 (December 2021) - Lam, Kenrick; Bui, Roger; Morris, Randal; Panchbhavi, Vinod
Background. Intramedullary screw fixation of Jones fractures using partially threaded screws is a common method of fixation for these injuries, but refracture continues to be a problem. Various other fixation strategies, such as headless compression screws, plantar plating, and tension-band wiring. have been developed to mitigate these issues. Biomechanical studies with regard to these other fixation strategies are limited. Herein, we investigate the compression strength and angular stiffness of Jones fractures fixed with Herbert-style headless compression screws. Methods. Jones fractures were created in 10 fresh-frozen pairs of cadaveric fifth metatarsals. A bone from each pair was instrumented with either a conventional, partially threaded screw 5.0 or 6.5 mm in diameter, or a headless compression screw 5.0 or 7.0 mm in diameter. Sizes were determined via sequential tapping until a snug fit was obtained. Each metatarsal was stressed via cantilever bending over 1000 cycles. We monitored compression and displacement throughout. Results. Headless compression screws achieved a significantly higher amount of stiffness than conventional, partially threaded screws (P = 0.005). There was no statistically significant difference with respect to compression. Conclusion. In a cadaveric model, headless compression screws achieved a greater amount of fracture stiffness versus conventional, partially threaded screws. Levels of Evidence: Therapeutic, Level V: Biomechanical